Argument Structure of Slide Verb in English (e-Journal of Linguistics, 2019)
Various languages in the world have their own systems, especially in terms of verbclassification. It can determine argument in the structure. This paper is intended to analyze theinteraction between syntax and semantics in terms of the argument structure of the slide verb inEnglish. The main theory used in this study was the theory of argument structure proposed byKim & Sells (2008). The result of analysis showed that two kinds of slide verb: bounce and slideare intransitive and transitive verbs. The specifier (SPR) of the sentence structure functions asthe agent; the Complement (COMPS) of the verb bounce serves as the patient and the COMPS ofthe verb slide functions as the theme.
Keywords: Slide Verb; Argument Structure; English